PENGARUH LATIHAN LONCAT TALI DAN LOMPAT KIJANG TERHADAP DAYA LEDAK OTOT TUNGKAI DALAM PERMAINAN BOLA VOLI PADA SISWA PUTRA KELAS VII SMPN 1 KERUAK KABUPATEN LOMBOK TIMUR TAHUN PELAJARAN 2015/2016 - Sahrial, Fery; Satrianingsih, Baiq; Subakti, Subakti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The problem in this research is the low leap of a volleyball player. The goal to be achieved in this research is to know how big "Influence of jumping skipping and skipping antelope to explosive muscle limb in game volleyball at grade VII students SMPN 1 keruak district east lombok lesson year 2015/2016 ". The method used to obtain the data in this research that is the documentation Â and experiment. After getting the value of t-count for the first alternative Hypothesis (Ha) is obtained at 3.020 then the value of t-table with degrees of freedom N = 10 at 5% significant level shows the figure of Â 2.228. Â This Â result Â means Â that Â t-count> Â t-table Â is Â 3.020> Â 2.228 Â orÂ with Â the Â null hypothesis rejection limit (Ho) listed in the table value of "t", while for the second alternative hypothesis that t-count> t-table is 3.020> 2.228 or with the limit of rejection of the null hypothesis (Ho) listed in the table value of "t", As for the second alternative hypothesis obtained t-count value of 2.539. This result means t-count> t-table that is 2,539> 2,228. Based on the above fact that the value of t-count is greater than t-table, thus the value "t" obtained in this study is significant. Then the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) "is rejected". It can be concluded that in this research "There is the Influence of Skipping Rope and the Kijang Skip to Explosive Muscle Limb In Volley Games On Male Student of Grade VII SMPN 1 Keruak East Lombok Academic Year 2015/2016â€.